Anticancer Activity of Oecophylla smaradina against Dalton’s Lymphoma Ascites Induced Tumor - Balamurugan K (Journal of Global Pharma Technology, 2018)
Objective to evaluate Oecophylla smaragdina (OS) for antitumor activity against Dalton's Lymphoma Ascites (DLA) cells in Swiss mice. Materials and Methods Oecophylla smaragdina (OS)was successively extracted with ethanol for three times and the treatment was started after 24 hours of the tumor inoculation continued once daily for 14 days and the antitumor efficacy of ant extract of Oecophylla smaragdina was compared with that of 5-Fluorouracil(10 mg/kg, i.p) and DLA control. After 14 days the mice was sacrificed and dissected for observation of antitumor activity. Results Oecophylla smaragdina extract treated group showed decrease in packed cell volume, viable cell count. The all the parameters were showed in normal levels. Conclusion the findings and indicate the ant extract to promote and preventing the tumor cells and also it is evident that these extract have natural anticancer effect.Keywords: Oecophylla smaragdina, Antitumor, Dalton’s lymphoma ascites.